Cactus Weevils, Gerstaeckeria hubbardi (LeConte) and Gerstaeckeria fasciata Pierce (Insecta: Coleoptera: Curculionidae) - Robert E. Woodruff (EDIS)
EENY-382, a 4-page illustrated fact sheet by Robert E. Woodruff, is included in the Featured Creatures series. It describes these two weevil pests of Opuntia cacti, their synonymy, distribution, description, biology, key to the Florida Species of Gerstaeckeria, hosts, management, and selected references. Published by the UF Department of Entomology and Nematology, July 2006.